Pantangan Melakukan Perkawinan Pada Bulan Suro di Masyarakat Adat Jawa Perspektif Hukum Islam - Masrukan Maghfur; Ahmad Hafid Safrudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
It is certainly no stranger to hear about the prohibition on getting married in the month of Suro or Muharrom, that Javanese customs have their predecessors' customs or traditions, not only in the month of Shuro, regarding beliefs regarding times, days and months that are standardized. This belief is considered inappropriate for carrying out sacred events such as weddings or circumcisions. This is because many Javanese people still maintain the customs or traditions handed down by their ancestors, even though some of them no longer believe in these things. This kind of tradition is still carried out from generation to generation to this day. However, will Islam justify this tradition if it is linked to the texts of the Qur'an and hadith, researchers will provide a descriptive description and analysis through inductive thinking. This research provides a discourse that it is forbidden to marry in the month of Suro or Muharrom in Javanese society because philosophically this month contains historical events that remind of tragic and emotional stories in it.